Sprawozdanie z Piątego Międzynarodowego Kongresu ISCAR "Taking a 360° view of the landscape of cultural-historical activity research: The state of our scholarship in practice" - Beata Zamorska; Przemysław Gąsiorek (University of Lower Silesia, 2017)
nie dotyczy